Pendugaan Densitas Karbon Pada Tegakan Pohon di Kawasan Hutan Kampung Sawesuma, Distrik Unurum Guay, Kabupaten Jayapura - Ziyadatun Ni'mah; Rosye H.R. Tanjung; Hendra K. Maury (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
The community managed conservation area forest (AKKM) of Kampung Sawesuma is part of the lowland forest landscape of Northern Papua. Lowland forests have a very high diversity of plant species and act as carbon sinks stored in tree stands. To determine the amount of carbon stored in tree stands, an estimation of the carbon density of tree stands was carried out in the AKKM forest area of Kampung Sawesuma, Jayapura. Estimation of carbon density was carried out by non-destructive method of tree stands using sample plots (measurement transects) and calculating tree biomass using allometric equations. The measurement results show that the tree biomass in the AKKM forest area is 167.5 tons/ha with an estimated carbon density of 78.7 tons/ha in the stands. Key words: carbon density; lowland forest; Sawesuma Village.